2003
DOI: 10.1523/jneurosci.23-03-00927.2003
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Calcium Transients in Developing Cortical Neurons Regulate Axon Outgrowth

Abstract: Growth cones of cortical axons pause for many hours in preparation for axon branching. They become large and complex compared with small advancing growth cones. We wanted to investigate whether calcium transients regulate the advance of mammalian CNS growth cones. We found that spontaneous calcium transients in developing cortical neurons have characteristic patterns, frequencies, and amplitudes. Importantly, neurons with large paused growth cones exhibit high-frequency spontaneous calcium transients, which ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
98
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(115 citation statements)
references
References 41 publications
(62 reference statements)
15
98
1
Order By: Relevance
“…Whereas some studies suggest that reducing intracellular levels of calcium can promote growth cone motility and neurite extension (Tang et al 2003), other studies suggest that lowering calcium inhibits these morphological features (Suarez-Isla et al 1984;Mattson and Kater 1987;Cambray-Deakin and Burgoyne 1992), consistent with observations described here. However, even within the same study, both low and high neuronal calcium levels have been shown to induce growth cone collapse (Mattson and Kater 1987;Kater et al 1988), suggesting that growth cone motility, as well as neurite growth and arborization, may require optimal levels of calcium, deviations above or below which result in negative outcomes.…”
Section: Calcium and Neuronal Maturationsupporting
confidence: 89%
“…Whereas some studies suggest that reducing intracellular levels of calcium can promote growth cone motility and neurite extension (Tang et al 2003), other studies suggest that lowering calcium inhibits these morphological features (Suarez-Isla et al 1984;Mattson and Kater 1987;Cambray-Deakin and Burgoyne 1992), consistent with observations described here. However, even within the same study, both low and high neuronal calcium levels have been shown to induce growth cone collapse (Mattson and Kater 1987;Kater et al 1988), suggesting that growth cone motility, as well as neurite growth and arborization, may require optimal levels of calcium, deviations above or below which result in negative outcomes.…”
Section: Calcium and Neuronal Maturationsupporting
confidence: 89%
“…Calcium imaging and analysis were performed as previously described (Tang et al, 2003;Tang and Kalil, 2005). Briefly, 18 -72 h after plating cell cultures were loaded with 4 M Fluo4 AM (Invitrogen) for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…In most cases, calcium activity was measured in the axon or the growth cone and levels of intracellular Ca 2ϩ were found to be inversely correlated with rates of axon outgrowth (Gomez and Spitzer, 1999;Tang et al, 2003;Jacques-Fricke et al, 2006) or changes in the direction of axon growth (Nishiyama et al, 2003;Wen et al, 2004). In previous studies, we found that global Ca 2ϩ transients inhibited extension of the primary axon (Tang et al, 2003), whereas localized Ca 2ϩ transients evoked by netrin-1 signaling could promote branching of the axon in regions of high-frequency Ca 2ϩ transients (Tang and Kalil, 2005). It has been well established that competitive activity-dependent mechanisms can regulate synaptic innervation at target sites.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic Ca 2+ changes have been reported in the developing cortex (Yuste et al 1992) and these Ca 2+ transients could be responsible for the axonal outgrowth. Th e incidence of Ca 2+ transients highly correlated with axonal growth cone morphologies and behaviors (Tang et al 2003).…”
Section: Th E Role Of Calcium In Neurite Growthmentioning
confidence: 99%